Public Policies and Exports of Cacao of Peru. Period 2011-2016 - Cárdenas Guerra, Raúl Armando (2019)
Objective: To analyze the application of public policies for the promotion of cocoa in Peru, during the period 2011-2016, with the proposal to determine the impact of these policies on the behavior of cocoa exports. Method: the research was a mixed design: exploratory (qualitative) and descriptive (quantitative) and documentary, which analyzes the behavior of exports and applied public policies. Results: The implementation of public policies has developed the increase in hectares planted and tons produced, favoring the increase in cocoa exports. Conclusions: Public policies in Peru applied to cocoa have achieved an increase in their export, according to the ITC1 from 32,997 tons in 2011 to 80,047 tons in 2016, however, this effort means less than one third of Ecuador’s export, ( 31.64% of 253,018 tons), so policies must be replaced in order to increase our exports.